Phthalocyanine-nanoparticle conjugates supported on inorganic nanofibers as photocatalysts for the treatment of biological and organic pollutants as well as for hydrogen generation - Mapukata, Sivuyisiwe (Rhodes University, Faculty of Science, Department of Chemistry)
This thesis reports on the synthesis, photophysicochemical and photocatalytic properties of various zinc phthalocyanines (Pcs). For enhanced properties and catalyst support, the reported Pcs were conjugated to different nanoparticles (NPs) through chemisorption as well as amide bond formation to yield Pc-NP conjugates. For increased catalyst surface area and catalyst reusability, the Pcs and some of their conjugates were also supported on electrospun inorganic nanofibers i.e. SiO2, hematite (abbreviated Hem and has formula Î±-Fe2O3), ZnO and TiO2 nanofibers. The effect that the number of charges on a Pc has on its antimicrobial activities was evaluated by comparing the photoactivities of neutral, octacationic and hexadecacationic Pcs against S. aureus, E. coli and C. albicans. The extent of enhancement of their antimicrobial activities upon conjugation (through chemisorption) to Ag NPs was also studied in solution and when supported on SiO2 nanofibers. The results showed that the hexadecacationic complex 3 possessed the best antimicrobial activity against all three microorganisms, in solution and when supported on the SiO2 nanofibers. Covalent conjugation of Pcs with carboxylic acid moieties (complexes 4-6) to amine functionalised NPs (Cys-Ag, NH2-Fe3O4 and Cys-Fe3O4@Ag) resulted in enhanced singlet oxygen generation and thus antibacterial efficiencies. Comparison of the photodegradation efficiencies of semiconductor nanofibers (hematite, ZnO and TiO2) when bare and when modified with a Pc (complex 6) were evaluated. Modification of the nanofibers with the Pc resulted in enhanced photoactivities for the nanofibers with the hematite nanofibers being the best. Modification of the hematite nanofibers with two different Pcs i.e. monosubstituted (complex 5) and an asymmetrical tetrasubstituted Pc (complex 6) showed that complex 6 better enhanced the activity of the nanofibers. Evaluation of the hydrogen generation efficiencies of the bare and modified TiO2 nanofibers calcined at different temperatures demonstrated that the anatase nanofibers calcined at 500 oC possessed the best catalytic efficiency. The efficiency of the TiO2 nanofibers was enhanced in the presence of the Co and Pd NPs as well as a Pc (complex 7), with the extent of enhancement being the greatest for the nanofibers modified with the Pd NPs. The reported findings therefore demonstrate the versatility of applications of Pcs for different water purification techniques when supported on different nanomaterials.
Keywords: Phthalocyanines; Nanofibers; Nanoparticles; Zinc; Hydrogen; Organic water pollutants; Water -- Purification; Electrospinning; Photocatalysis; Photodegradation; Anti-infective agents